A Survey on the Use of Haptic Feedback for Brain-Computer Interfaces and Neurofeedback - Fleury, Mathis; Lioi, Giulia; Barillot, Christian; Lécuyer, Anatole (Frontiers in Neuroscience, 2020)
Neurofeedback (NF) and Brain Computer Interface (BCI) rely on the registration and real-time feedback of an individual brain activity with the aim of achieving self-regulation of specific neural substrate or controlling external devices. These approaches have historically employed visual stimuli. However, in some cases vision is not suitable or inadequately engaging. Other sensing modalities like auditory or haptic feedback have already been explored and multisensory stimulation is expected to improve the quality of the interaction loop. Moreover, in the case of motor imagery task, closing the sensory-motor loop thanks to haptic feedback may be relevant for motor rehabilitation application, as it can promote plasticity mechanisms. This survey presents the various haptic technologies and then describes their application to BCI and NF. We identify major trends in the use of haptic interfaces for BCI and NF and discuss crucial aspects to inspire further studies.